Effect of Number of Seedlings Hill-1 and Rate and Time of Nitrogen Application on the Yield of Late Transplant Aman Rice (cv. Br23) - Ali, N.A.M.Y.; Sarkar, M.A.R.; Paul, S.K. (International Journal of Applied Sciences and Biotechnology, 2015)
A field experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh to examine the effect of number of seedlings hill‑1 and rate and time of nitrogen application on the yield of late transplant Aman rice (cv. BR23). The experiment comprised three levels of number of seedlings hill-1 viz. 2, 4, and 6, three nitrogen rates viz. 0, 60 and 120 kg N ha-1 and three levels of time of nitrogen application viz. nitrogen application in two equal splits at 15 DAT and early tillering stage (ET); nitrogen application in three equal splits at 15 DAT, ET and panicle initiation (PI) stage; nitrogen application in four equal splits at 15 DAT, ET, PI and flowering (F) stages. The experiment was laid out in a randomized complete block design with three replications. Number of effective tillers hill‑1, grain yield and straw yield were the highest when 6 seedlings were transplanted hill‑1 while all yield contributing characters, grain and straw yields were the highest at 120 kg N ha-1. In case of interaction, the highest grain yield was recorded in combination of 6 seedlings hill-1 × 120 kg N ha-1 and 120 kg N ha-1 × three times of nitrogen applications (15 DAT + ET + PI). The highest number of effective tillers hill-1 and grain yield were recorded in 6 seedlings hill-1 × 120 kg N ha-1 × three times N application (15 DAT + ET + PI) and thus this practice appears as the promising one for late transplant Aman rice ( cv. BR23) cultivation. Int J Appl Sci Biotechnol, Vol 3(4): 692-698